2011
DOI: 10.1007/s00068-011-0119-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell (MSC) and endothelial progenitor cell (EPC) growth and adhesion in six different bone graft substitutes

Abstract: When bone graft substitutes are used to help fill large defects, it is important that their interaction with these cells be supportive of bone healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…In a few in vitro experiments, bone substitutes were combined with BM-MSCs and endothelial progenitor cells (EPCs). It was shown that MSCs can attach to artificial scaffolds that prolong their vitality [20]. Furthermore, a few in vivo studies have indicated that ADSCs secrete large amounts of bone morphogenetic proteins (BMPs), which accelerate osteogenesis [21].…”
Section: The Use Of Selected Sc Fractions In Plastic and Reconstructimentioning
confidence: 99%
“…In a few in vitro experiments, bone substitutes were combined with BM-MSCs and endothelial progenitor cells (EPCs). It was shown that MSCs can attach to artificial scaffolds that prolong their vitality [20]. Furthermore, a few in vivo studies have indicated that ADSCs secrete large amounts of bone morphogenetic proteins (BMPs), which accelerate osteogenesis [21].…”
Section: The Use Of Selected Sc Fractions In Plastic and Reconstructimentioning
confidence: 99%
“…Bu konuda yapılan deneysel çalışmalar artık kliniğe uygulanır hale gelmiştir. Mezenkimal kök hücrelerin canlılıklarını sürdürebilmek için bir iskelet formu (scaffold) üzerine yerleştirilerek eklenebildiği ve burada işlevsel olarak çoğalabildiği bilinmektedir (23) . Çocuk cerrahisinde damak plastiği yapılırken alveolar cleft rekonstrüksiyonun da kemik iliği kökenli kök hücrelerin kullanımının deneysel düzeyden çıktığı ve klinik uygulamalara dönüştüğü bildirilmektedir (24) .…”
Section: Rekonstrüktif Cerrahiunclassified
“…ACTIFUSE â (APATECH Baxter), a moldable bone graft, is made from silicate substituted calcium phosphate and is 100 percent synthetic. ACTIFUSE â has been shown to be osteostimulative with minimal complications [6,7]. However, it is mainly utilized to repair small defect volumes and is contraindicated for structural and load bearing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several options exist however each has limitations. Allografts offer organized natural bone material however there is the possibility of infection or rejection of the donor material [6,7]. Ceramic materials have been used alone and after doping with growth factors and are much less of a risk to the patient [7,8].…”
Section: Introductionmentioning
confidence: 99%